IMPACT ON MENTAL HEALTH OF UNDERGRADUATES AND THE WAYS TO COPE STRESS DURING COVID-19 PANDEMIC - Bana, Kiran Fatima (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the mental health status of undergraduate’s students of three different programs. To correlate the related factors influencing GAD-7 score and to assess the coping methods practiced by undergraduates during COVID-19 outbreak.Study Design: Cross-sectional survey.Place and Duration of Study: COVID-19 lock down period among public and private universities in Karachi, from 10th May to 30th May 2020.Methodology: It was conducted among the medical, dental and engineering students of private sector universities of Karachi. The GADS-7 (Generalized anxiety disorder scale 7-items) validated tool was used along with the demographic variables, related stress factors and the coping skills practiced. Total 571 questionnaires were found completed in all sections.Results: From the total students 132 (23.1%) experienced mild, 343 (60.1%) moderate and 78 (13.7%) had severe anxiety level on GADS-7. All related stressors were significantly associated with GAD-7 scale at p-value of